2019
DOI: 10.1111/jgh.14736
|View full text |Cite
|
Sign up to set email alerts
|

Short‐term and long‐term impacts of Helicobacter pylori eradication with reverse hybrid therapy on the gut microbiota

Abstract: Background and Aims:Anti-Helicobacter pylori therapy may lead to the growth of pathogenic or antibiotic-resistant bacteria in the gut. The study aimed to investigate the shortterm and long-term impacts of H. pylori eradication with reverse hybrid therapy on the components and macrolide resistance of the gut microbiota. Methods: Helicobacter pylori-related gastritis patients were administered a 14-day reverse hybrid therapy. Fecal samples were collected before treatment and at the end of week 2, week 8, and wee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
46
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(51 citation statements)
references
References 43 publications
5
46
0
Order By: Relevance
“…Previous multiple time‐point follow‐up studies found that alpha diversity was recovered 8 weeks after eradication 51 . Similarly, other researchers recorded alpha diversity at weeks 0, 2, 8, and 48 reporting that the value was recovered at week 8 as well 53 . In accordance with these reports, most studies gathering follow‐up information within 2 months showed a decreased alpha diversity, whereas studies gaining information thereafter frequently reported no significant differences with baseline 9,50,51,53‐57 .…”
Section: Gastrointestinal Microbiota Reshaping Upon Eradication Therapysupporting
confidence: 62%
See 1 more Smart Citation
“…Previous multiple time‐point follow‐up studies found that alpha diversity was recovered 8 weeks after eradication 51 . Similarly, other researchers recorded alpha diversity at weeks 0, 2, 8, and 48 reporting that the value was recovered at week 8 as well 53 . In accordance with these reports, most studies gathering follow‐up information within 2 months showed a decreased alpha diversity, whereas studies gaining information thereafter frequently reported no significant differences with baseline 9,50,51,53‐57 .…”
Section: Gastrointestinal Microbiota Reshaping Upon Eradication Therapysupporting
confidence: 62%
“…As a general trend, alpha diversity tended to decrease immediately after eradication and reverted thereafter (Figure 2; Table 4). 50‐53 Specifically, how much time is needed for restoration remains to be elucidated. Previous multiple time‐point follow‐up studies found that alpha diversity was recovered 8 weeks after eradication 51 .…”
Section: Gastrointestinal Microbiota Reshaping Upon Eradication Therapymentioning
confidence: 99%
“…We searched PubMed using the terms “Helicobacter”, “eradication” and “microbiota” for papers published from January 1, 2000, to March 12, 2020, in English. Sixteen studies using high‐throughput sequencing to assess alterations in the gut microbiota before and after H pylori eradication are summarized in Table 17‐32 . 10 publications focus on the impact of standard triple therapy and 5 studies address the long‐term (at least one year) effect after treatment.…”
Section: Introductionmentioning
confidence: 99%
“…The increased antibiotic resistance in H. pylori will further reduce patients' quality of life and increase the cost-effectiveness of antibiotic-based therapy [ 8 ]. In addition, prolonged eradication therapy for H. pylori infection also leads to dysbiosis of the intestinal microbiota and increases the expression of resistance genes, which may further induce various diseases [ 12 , 15 , 16 , 29 ]. However, with the emergence of WMT and fecal suspension capsules, the safety and convenience of WMT have been significantly improved [ 23 , 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that H. pylori infection causes gastrointestinal microbiota disorder, and this change is reversible after H. pylori eradication [ 12 14 ]. In addition, antibiotic-based treatments for H. pylori eradication have been shown to cause gut microbiota dysbiosis and lead to the increase of erm (B) gene (a gene encoding erythromycin-resistant methylase), which would compromise the efficacy of eradiation therapy regimens including a macrolide [ 12 , 15 , 16 ]. Therefore, it may be possible to reverse the colonization of H. pylori by restoring the gastrointestinal microbiota.…”
Section: Introductionmentioning
confidence: 99%